“It is Permitted for the Amīr but not the Qāḍī”: The Military-Administrative Genealogy of Coercion in Abbasid Criminal Justice - Allehbi, Mohammed (Islamic law and society, 2023)
Muslim rulers and law enforcers used coercion as an evidentiary method for criminal cases during the Abbasid period. These coercive procedures consisted of imprisonment, threats of beatings, and lashings. Coercive interrogations were shaped by the practices of the shurṭa (criminal magistrates and police chiefs), based on military methods, administrative precedents, and discretion, not on fiqh (Islamic substantive law). In the Abbasid era (300–500 A.H./900–1100 C.E.), government officials, such as Ibn Wahb (d. after 335/946), and even some jurists, particularly the chief judge al-Māwardī (d. 450/1058), legitimized these coercive practices by framing their use as a matter determined by authority and jurisdiction. By tracing the military-administrative genealogy of coercion, I seek to examine the methods and reasoning that constituted the criminal justice system that came to be known as siyāsa. Drawing on various administrative and literary sources, I examine a history of coercion in Islamic law beyond fiqh.